Debt-Trap Diplomacy: Bagaimana Ekspansi Kapital China Membentuk Jebakan Utang Bagi Negara-Negara Afrika - Faris Al-Fadhat; Hari Prasetio (Jurnal Ilmiah Hubungan Internasional, 2022)
Since the Belt and Road Initiative (BRI) was initiated in 2013, China under Xi Jinping has continued to expand its capital to various countries. This expansion is part of China’s strategy to shore up its position as a global major economic and political power vis a vis the United States. As nearly 70 countries have joined the BRI network, this economic cooperation scheme contributes to economic growth as well as helps to close the infrastructure gap. Nevertheless, not all countries experienced equal development through economic cooperation with China. Some are dependent and even facing a debt-trap as shown in the case of African countries. This article addresses the question why such economic cooperation has turned into a debt-trap for countries in the African region. Applying the concept of Structural Power in examining China’s investment in three countries namely Zimbabwe, Cameroon, and Djibouti, this article argues that the debt-trap has caused by the structural disparity between China as an investor and African countries as investment recipients. China, in this case, has a more dominant “good” aspect, while African countries are more in “need”. This article also contends that the debt-trap is a strategy carried out by Chinese government to dominate the African economies.